Which surgical treatment for Dupuytren’s Contracture is most cost-effective in England? - Singh, G (2020)
Objectives: To assess the cost-effectiveness of surgical interventions offered in the NHS for adults with Dupuytren’s contracture admitted into secondary care, when compared to the mainstay of surgical treatment (Limited Fasciectomy).